A bionic tree-liked fractal structure as energy absorber under axial loading. (15th October 2021) - Wu, Jiacheng; Zhang, Yong; Zhang, Feng; Hou, Yubo; Yan, Xiaolei
Highlights: A bionic tree-liked fractal method is introduced to design an energy absorber with high crashworthiness. The theoretical model is developed to predict the energy absorption of the tree-liked fractal structure. The fractal coefficient and wall thickness have significant effect on energy absorption. The 3rd order tree-liked fractal structure has higher energy absorption than typical multi-cell structure. Abstract: A tree-liked fractal method is proposed to develop a novel protective structure with great energy absorption. Triangular, square and pentagonal tree-liked fractal structures are developed, and their mechanical behaviors and deformation processes are conducted by quasi-static axial crushing testing. The theoretical model of the tree-liked fractal structure is introduced to analyze their energy absorption under quasi-static and dynamic loads. Then, the numerical comparative study of the tree-liked fractal structure on crushing characteristics is further carried out based on high accuracy finite element model. The tree-liked fractal structure has great potential to improve specific energy absorption and crash force efficiency compared with the single-walled structure, and the 3rd order tree-liked fractal structure exhibits the best carrying capacity. In addition, the parametric design is adopted to obtain an optimal fractal coefficient and the optimal distribution of the wall thickness of the 3rd order tree-like fractal structure. Furthermore, the crashworthiness comparison of 3rd order tree-like fractal structure and typical multi-cell structures with the same mass is performed to reveal the advantage for the energy absorption. The finding of this study offers an effective design concept for developing the lightweight and efficient energy absorber.